Virtual reality in anxiety disorders: the past and the future - Gorini, Alessandra; Riva, Giuseppe (Expert review of neurotherapeutics, 2008)
One of the most effective treatments of anxiety is exposure therapy: a person is exposed to specific feared situations or objects that trigger anxiety. This exposure process may be done through actual exposure, with visualization, by imagination or using virtual reality (VR), that provides users with computer simulated environments with and within which they can interact. VR is made possible by the capability of computers to synthesize a 3D graphical environment from numerical data. Furthermore, because input devices sense the subject's reactions and motions, the computer can modify the synthetic environment accordingly, creating the illusion of interacting with, and thus being immersed within the environment. Starting from 1995, different experimental studies have been conducted in order to investigate the effect of VR exposure in the treatment of subclinical fears and anxiety disorders. This review will discuss their outcome and provide guidelines for the use of VR exposure for the treatment of anxious patients.